An advanced joint time-frequency analysis procedure to study cavitation-induced noise by using standard series propeller data. (15th December 2018) - Aktas, Batuhan; Atlar, Mehmet; Fitzsimmons, Patrick; Shi, Weichao
Abstract: Underwater noise has attracted significant amount of interest in the last decade because of its potential impact on marine fauna. Commercial shipping is one of the major contributors. Amongst various sources on-board, cavitation dominates the overall radiated noise levels beyond its inception. Besides its significance, the mechanisms driving cavitation related noise and frequency regions that certain cavitation dynamics contribute into are not studied sufficiently. To address this gap in the literature, a study has been conducted to provide means of a plausible propeller cavitation noise prediction method and to provide enhanced insight to the noise creating mechanisms of cavitation by applying appropriate signal processing methods. Within this framework this study presents an advanced joint time-frequency analysis procedure to study cavitation-induced noise by using standard series propeller data. Systematic cavitation tunnel test are conducted with 6 members of the Meridian Standard propeller series that are carefully chosen to study the influence of major propeller design parameters such as Blade Area Ratio (BAR), Pitch to Diameter (P/D) ratio and blade number. Moreover, these propellers are tested behind systematically varied wake inflows reproduced by wake screens in addition to the open water conditions. Synchronized pressure pulse and noise measurements in combination with high-speed cavitation observations are then utilized to develop an advanced cavitation dynamics analysis tool to provide better insight into cavitation-induced noise. The analysis of the measurements has shown the significance of the cavitation on radiated noise levels and the impact of different cavitation dynamics in certain frequency regions.